Proposed Design of Knowledge-Based Performance Management System for an SME Clothing Brand - Muhamad Danindra Riansa; Dermawan Wibisono; Ima Fatima (Journal of Research in Social Science and Humanities, 2025)
CV. MD is a Bandung-based SME clothing brand founded in 2003, offering products such as T-shirts, pants, bags, shoes, caps, and accessories. With nine stores and numerous resellers across Indonesia, the company faces challenges like production delays, employee disengagement, and competition. This study proposes implementing a Knowledge-Based Performance Management System (KBPMS) to improve performance. The KBPMS framework is structured into five phases: (1) Foundation (2) Background Information; (3) Design Process; (4) Implementation Process; and (5) Refreshment. The focus of this study is on the design process. Twenty-one Key Performance Indicators (KPIs) were developed across three perspectives of KBPMS: business results, internal processes, and resource capabilities. The Analytic Hierarchy Process (AHP) was used to prioritize the KPIs importance. An implementation plan was also outlined for future use. Adopting KBPMS will enable CV. MD to monitor performance, reduce delays, improve productivity, and strengthen its competitive edge.